Single-step synthesis of Er3+ and Yb3+ ions doped molybdate/Gd2O3 core–shell nanoparticles for biomedical imaging. (6th December 2017) - Kamińska, Izabela; Elbaum, Danek; Sikora, Bożena; Kowalik, Przemysław; Mikulski, Jakub; Felcyn, Zofia; Samol, Piotr; Wojciechowski, Tomasz; Minikayev, Roman; Paszkowicz, Wojciech; Zaleszczyk, Wojciech; Szewczyk, Maciej; et al.
Abstract: Nanostructures as color-tunable luminescent markers have become major, promising tools for bioimaging and biosensing. In this paper separated molybdate/Gd2 O3 doped rare earth ions (erbium, Er 3+ and ytterbium, Yb 3+ ) core–shell nanoparticles (NPs), were fabricated by a one-step homogeneous precipitation process. Emission properties were studied by cathodo- and photoluminescence. Scanning electron and transmission electron microscopes were used to visualize and determine the size and shape of the NPs. Spherical NPs were obtained. Their core–shell structures were confirmed by x-ray diffraction and energy-dispersive x-ray spectroscopy measurements. We postulated that the molybdate rich core is formed due to high segregation coefficient of the Mo ion during the precipitation. The calcination process resulted in crystallization of δ / ξ (core/shell) NP doped Er and Yb ions, where δ —gadolinium molybdates and ξ —molybdates or gadolinium oxide. We confirmed two different upconversion mechanisms. In the presence of molybdenum ions, in the core of the NPs, Yb 3+ – MoO 4 2 − (∣ 2 F7/2, 3 T2 ⟩) dimers were formed. As a result of a two 980 nm photon absorption by the dimer, we observed enhanced green luminescence in the upconversion process. However, for the shell formed by the Gd2 O3 :Er, Yb NPs (without the Mo ions), the typical energy transfer upconversion takes place, which results in red luminescence. We demonstrated that the NPs were transported into cytosol of the HeLa and astrocytes cells by endocytosis. The core–shell NPs are sensitive sensors for the environment prevailing inside (shorter luminescence decay) and outside (longer luminescence decay) of the tested cells. The toxicity of the NPs was examined using MTT assay.